Historyczne formy waloryzacji ruin - Frydryczak, Beata (Studia Europaea Gnesnensia, 2011)
On the historical and cultural plane, ruins are a lasting element of our landscape. The attitude towards ruins evolved, yet eventually, the 18th and 19th century “cult of ru-ins” allowed them to be perceived from the perspective of aesthetics, which, associating ruins with the category of the picturesque and the sublime, rendered a new meaning to them. The principal thesis of the article rests on the assumption that the discovery of ruins was possible due to the recognition of the landscape’s aesthetic dimension, while their essence lies in their permeation into the world of nature, which allows them to live a natural time.